A metáfora da água na poética de Miguel Jorge - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
This study investigates the metaphor of water in the poetics of Miguel Jorge. For that, we have selected poems from four of the writer's literary books – which are: Os frutos do rio (1974), Profugus (1990), Calada nudez (1999) e Marbrasa (2004) – to constitute the corpus. The readings made indicate that water is a subject versed in almost all the poems of the author, appearing with greater emphasis on the chosen books. We analyze the metaphorical configurations of this element as a symbol that is associated with the sacred and the profane, contributing to configure the lyrical subject and the enunciative voice within the poems. The “Instauração Praxis” and eroticism were also contemplated in our analytical course for the attempt to understand poetry by Miguel Jorge. Turning to the update of the myth, in this approach, we find that the focused poems revive mythologemas and archetypal models related to the investigated element. Finally, in order to read the work of Miguel Jorge, we use the theoretical contributions of Mario Chamie (1974), Gaston Bachelard (1988, 2013), Georges Bataille (1988), Octavio Paz (2001), Raíssa Cavalcante (1999), among others.
The metaphor of water in the poetics of Miguel Jorge
Keywords: Miguel Jorge; Metáfora; Água; Poesia; Mito; Metaphor; Water; Poetry; Myth; LINGUISTICA, LETRAS E ARTES